Common Property Resources : Ecology & community-based sustainable development / (Acc. 3875) - Berkes Frkret; Chamola, B. P.; Chauhan, D. S. (Dhanpal Singh), 1969-; H.N. Bahuguna Garhwal University. Dept. of Forestry; India. Planning Commission (Dehradun. International Book Distributors, 2008)
Seminar held at HNB Garhwal University on November 1-3, 2006.
Keywords: Forestsand forestry